Rapid screening of adipogenic responses to EGCG in non-induced L929 adipocytes using image-based analysis compared to the conventional 3T3-L1 method - Kewalin Inthanon,, Rungnapa Sririwichitchai, Neal M. Davies (Journal of Applied Pharmaceutical Science, 2025)
Adipogenesis research often necessitates lengthy induction protocols and intricate biochemical assays to assess lipid accumulation, posing challenges for rapid screening of substances affecting fat cell formation. The purpose of this study is to present a novel, expedited approach utilizing L929 cells and image-based analysis to evaluate the adipogenic response to (-)-epigallocatechin gallate (EGCG). The L929 cells, known for their spontaneous adipocyte differentiation potential, were selected as an alternative to the conventional 3T3-L1 cell model. Unlike 3T3-L1 cells, which require a 10–14-day induction period, L929 cells differentiated into mature adipocytes within just 5 days, significantly reducing the processing time. Our results demonstrate that L929 cells exhibit greater sensitivity to EGCG compared to 3T3-L1 cells, with a dose-dependent decrease in viability observed after 72 hours of exposure. Despite this difference in sensitivity, both cell types displayed consistent anti-adipogenic responses and gene expression trends when treated with EGCG. Specifically, EGCG treatment resulted in the downregulation of adipogenic genes such as PPARγ, C/EBPα, aP2, and Pref-1, indicating a similar mechanism of action in both cell lines. The image-based assay employed in this study enabled precise quantification of cellular parameters, facilitating objective and reproducible assessments of adipogenic responses without the need for biochemical evaluation of lipid accumulation. Our findings suggest that the combined use of L929 cells and image-based analysis provides a reliable, cost-effective, and time-efficient method for preliminary screening of anti-adipogenic substances. This streamlined approach holds promise for advancing adipogenesis research by offering a practical alternative to traditional methods while maintaining robust and reproducible results.
Keywords: Adipogenesis, EGCG (epigallocatechin gallate), L929, 3T3-L1, image-based assay, anti-adipogenesisa